Preservation of the left ventricle contractility while performing of the combined mitral-aortal failure correction - A. A. Bolshak; V. Zh. Boukarim; K. E. Vakulenko; R. M. Vitovskiy; Yu. V. Bakhovska; N. I. Volkova; E. V. Yuvchik; V. V. Popov; V. V. Lazorishinets (Клінічна хірургія)
Objective. The studying of possibilities of procedures, directed on preservation of left ventricle while doing a mitral valve prosthesis in operative correction of combined mitral-aortal failure.